Micro Welding of Ni-based Alloy Monel 400 Thin Foil by Pulsed Nd:YAG laser - Ventrella, Vicente Afonso [UNESP]; Berretta, Jose Roberto; de Rossi, Wagner (Elsevier B.V., 2011)
In this study a pulsed Nd:YAG laser was used to join Monel 400 thin foil with 100 mu m thickness. Pulse energy was varied from 1.0 to 2.25J at small increments of 0.25J. The macro and microstructures were analyzed by optical microscopy, tensile shear test and microhardness. Sound laser welds without discontinuities were obtained with 1.5 J pulse energy. Results indicate that using a precise control of the pulse energy, and so a control of the bottom foil dilution rate, it is possible to weld Monel 400 thin foil. The process appeared to be very sensitive to the gap between couples.
Keywords: Laser welding; Nd:YAG; Monel 400; Thin foil; Tensile shear test